H4 Receptor Inhibits Lipopolysaccharide-induced NF-κB Activation by Interacting with Tumor Necrosis Factor Receptor-Associated Factor 6. (1st February 2019) - Shan, Yanfeng; Gao, Yining; Zhang, Li; Ma, Lili; Shi, Yuwen; Liu, Xia
Highlights: H4R expression increased in a rat model of lipopolysaccharide (LPS)-induced CNS inflammation. Overexpression of H4R in microglial HAPI cells decreased the production of proinflammatory cytokines following LPS stimulation. Knockdown of H4R enhanced proliferation and migration in LPS-treated microglia. An interaction between H4R and tumor necrosis factor receptor-associated factor 6 (TRAF6) was observed in microglia. Abstract: Microglia, the resident immune cells of the central nervous system (CNS), are activated at the beginning of the inflammatory response and induce detrimental neuroinflammation by producing excessive pro-inflammatory cytokines. Nuclear factor kappa B (NF-κB) signaling facilitates the onset of microglia activation. However, the molecular mechanisms underlying the negative regulation of NF-κB remain to be fully elucidated. In the present study, our results indicated that H4R expression increased in a rat model of lipopolysaccharide (LPS)-induced CNS inflammation. Knockdown of H4R in microglia HAPI cells enhanced the production of cytokines following LPS stimulation. Co-immunoprecipitation experiments further revealed an interaction between H4R and tumor necrosis factor receptor-associated factor 6 (TRAF6) in microglia, which was verified both in vivo and in vitro . Our experimental results support our hypothesis that H4R interacts with TRAF6 to inhibit the release of inflammatory cytokines in LPS-induced microglia cells by decreasing TRAF6-mediated ubiquitination of K63. These findings provide theoretical and experimental evidence regarding the role of H4R in the microglia inflammatory response, which may aid in the development of novel treatments for inflammation.